Maternal anxiety and diet quality among mothers and toddlers from low‐income households - Angela C. B. Trude; Maureen M. Black; Pamela J. Surkan; Kristen M. Hurley; Yan Wang (Wiley, 2020)
Abstract We evaluated the association between maternal anxiety score and diet quality over time among mothers and toddlers in low‐income families. Longitudinal data were collected from 267 mother-toddler dyads in an obesity prevention trial. Participants were recruited from the Special Supplemental Nutrition Program for Women, Infants and Children and paediatric clinics between 2007 and 2010. Dyads were assessed at study enrolment (Time 1), 6‐month (Time 2), and 12‐month follow‐up (Time 3). On the basis of a 1‐day 24‐hr dietary recall, we estimated maternal and toddler diet quality using the Healthy Eating Index 2015. Anxiety, a time‐varying variable, was assessed via the State-Trait Anxiety Inventory. Associations between maternal anxiety score and maternal and toddler diet quality over time were assessed in adjusted mixed models. Maternal and toddler diet quality were positively correlated (r = .48, p < .001). Higher maternal anxiety scores were related to lower toddler Healthy Eating Index scores (b = −0.51, 95% confidence interval, CI [−0.87, −0.15]) with no significant variation over time. The relation between maternal diet quality and anxiety score varied over time (b = 0.28, p = .03, for time-anxiety interaction). Higher maternal anxiety scores were associated with lower maternal diet quality at Time 1 (b = −0.71, 95% CI [−1.09, 0.34]) and at Time 2 (b = −0.51, 95% CI [−0.97, −0.05]), but not at Time 3 (b = −0.14, 95% CI [−0.54, 0.26]). Findings suggest that mothers and toddlers exhibited similar low‐quality dietary patterns and that lower diet quality was associated with higher maternal anxiety scores. Approaches to enhance diet quality may consider incorporating anxiety‐reducing strategies into maternal and toddler care and feeding behaviour guidelines.